Effect of laser processing parameters on the formation of intermetallic compounds in Fe-Al dissimilar welding - Meco, Sonia; Ganguly, Supriyo; Williams, Stewart W.; McPherson, Norman (Springer, 2014)
Fusion welding of steel to aluminum is difficult due to formation of different types of Fe-Al intermetallics (IMs). In this work, 2mm-thick steel was joined to 6mm aluminum in overlap configuration using a 8kW CW fiber laser. A defocused laser beam was used to control the energy input and allow melting of the aluminum alone and form the bond by wetting of the steel substrate. Experimentally, the process energy was varied by changing the power density (PD) and interaction time separately to understand the influence of each of these parameters on the IM formation. It was observed that the IM formation is a complex function of PD and interaction time. It was also found that the mechanical strength of such joint could not be simply correlated to the IM layer thickness but also depends on the area of wetting of the steel substrate by molten aluminum. In order to form a viable joint, PD needs to be over a threshold value where although IM growth will increase, the strength will be better due to increased wetting. Any increase in interaction time, with PD over the threshold, will have negative effect on the bond strength.